A Low-Complexity Spectral Shaping Method for OFDM Signals with Dynamically Defined Emission Mask: Optimization Procedure. - Giménez, Javier; Cortés-Arrabal, José Antonio; Díez-del-Río, Luis (My University, 2023)
The low spectral confinement of orthogonal frequency division multiplexing (OFDM) signals obliges OFDM based power line communications (PLC) systems to use out-of-band emissions (OOBE) reduction methods in order to comply with electromagnetic compatibility (EMC) regulations. This work proposes a computationally simple optimization procedure that yields a versatile set of solutions to shape the spectrum of OFDM signals regardless of the location and width of its passbands.
Keywords: Multiplexación; Telecomunicaciones; Optimización matemática; OFDM; Comunicaciones; Espectro; Conformado; Comunicaciones digitales; Conformación espectro